Application of electrodialysis for lactic acid recovery - V. Hábová; K. Melzoch; M. Rychtera; L. Přibyl; V. Mejta (Czech Journal of Food Sciences, 2001)
The paper deals with the possibility of using two-stage electrodialysis for recovery of lactic acid from model solutions and from fermentation broth. In the first step lactate was concentrated with desalting electrodialysis using ion exchange membranes Ralex (Mega,Czech Republic). The highest final concentration of 111 g/l was reached in the concentrate, it means an increase more than 2.5-times in comparison with the initial concentration. At the most 2 g of lactate per litre remained in the feed. The second step was the electroconversion of sodium lactate to lactic acid by water-splitting electrodialysis with the bipolar membranes Neosepta (Tokuyama Corp.,Japan). The final lactic acid concentration of 157 g/l was reached in the diluate. Total required energy in both electrodialysis processes consisting of the energy consumption for lactate transfer and for its electroconversion to lactic acid was 142 Wh/mol. The fermentation broth was decolourised before electrodialysis experiments. The best decolourisation capacity was shown by granulated active charcoal filled in the column operated by a slow flow of broth.